ASSESSMENT OF PAIN AND FUNCTION IN PATIENTS WITH CHRONIC LOW BACK PAIN SUBJECT THE ELECTROSTIMULATION WITH BERNARD'S DIADYNAMIC CURRENT ASSOCIATED OR NOT THE IONTOPHORESIS. (Fiep Bulletin - online, 2012)
Low back pain is caused by conditions such as: congenital, degenerative, inflammatory, infectious, tumor and mechanical postural. The physical therapy modalities may be useful in this situation, highlighting the electrotherapy and the use of the same seeking of iontophoresis application. Thus, the aim of this study was to analyze the effects on pain and function, of Bernard´s Diadynamic current associated or not the iontophoresis with sodium salicylate 3% in patients with chronic low back pain. The sample comprised 21 patients who were randomly divided into two groups: one received the application Bernard's Diadynamic Current, composed of 10 patients (G1) and another was associated with iontophoresis, composed of 11 patients (G2). It was used as an instrument of evaluation, the Visual Analog Scale of Pain (VAS), the Dolorimeter of Pressure, and the Oswestry questionnaire and McGill. Comparing the results with the use of VAS, the treatment was effective in two ways used, as compared to the Oswestry questionnaire, the treatment was beneficial only with the Bernard's Diadynamic Current associated with iontophoresis. However, the use of the Dolorimeter of Pressure as the McGill questionnaire, there was no significant difference between the two forms of treatment. It follows, then, that the Bernard´s Diadynamic current associated with iontophoresis, are effective in improving function in patients with low back pain, this being assessed by the Oswestry questionnaire. For the treatment of pain, assessed by VAS, both Bernard´s Diadynamic current isolated as the Bernard´s Diadynamic current associated with iontophoresis are effective in patients with chronic low back pain.
Keywords: Physical Therapy Modalities; low back pain; iontophoresis.